2019
DOI: 10.1186/s12884-019-2381-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal near miss determinants at a maternity hospital for high-risk pregnancy in northeastern Brazil: a prospective study

Abstract: Background To investigate the association between sociodemographic and obstetric variables and delays in care with maternal near misses (MNMs) and their health indicators. Methods A prospective cohort study was conducted at a high-risk maternity hospital in northeastern Brazil from June 2015 to May 2016 that included all pregnant women seen at the maternity hospital during the data collection period and excluded those who had not been discharged at the end of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
37

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 28 publications
4
33
0
37
Order By: Relevance
“…Nesta análise, observou-se que 11,6% das mulheres entrevistadas não realizaram nenhuma consulta pré-natal e dentre aquelas que fizeram o acompanhamento, 25,8% realizaram menos de seis consultas durante a gestação. Estudos apontam que a qualidade da assistência pré-natal, a baixa cobertura e a não realização de ao menos seis consultas são conhecidos fatores de risco para o near miss materno 35,36 .…”
Section: Discussionunclassified
“…Nesta análise, observou-se que 11,6% das mulheres entrevistadas não realizaram nenhuma consulta pré-natal e dentre aquelas que fizeram o acompanhamento, 25,8% realizaram menos de seis consultas durante a gestação. Estudos apontam que a qualidade da assistência pré-natal, a baixa cobertura e a não realização de ao menos seis consultas são conhecidos fatores de risco para o near miss materno 35,36 .…”
Section: Discussionunclassified
“…Maternal near miss determinants at a maternity hospital for high-risk pregnancy in northeastern Brazil: a prospective study (47) 2018 - High risk pregnancy associated perinatal morbidity and mortality: a second birth population-based survey in Huai'an in 2015 (48) 2019 Symbiotic maternalfetal relationship.…”
Section: Title Year Attributes Antecedentsmentioning
confidence: 99%
“…Negative pregnancy outcomes are strongly influenced by risk factors. Such risk factors trigger problems during pregnancy, making the mother and fetus vulnerable to complications and morbidities (44)(45)(46)(47)(48)(49)(50)(51)(52) .…”
Section: Study Limitationsmentioning
confidence: 99%
“…This rate is largely variable on literature depending on the geographic region, hospital and obstetric care, but it is known that, in comparison to other studies and populations, this is an extremely high number. A national Brazilian study 8 reported a MNM ratio of 10.2, while a study with high-risk pregnancies reported a rate of 54.8 9 . To the best of our knowledge, SMM in T1DM has not yet been studied.…”
Section: Discussionmentioning
confidence: 98%